Silicon-carbon composite material, preparation method and battery

By adopting a composite structure of porous silicon and amorphous carbon in the battery material and forming a composite cladding layer containing lithium inorganic substances on its surface, the problem of poor electrical performance of existing silicon-carbon materials is solved, and better rate performance and cycling performance are achieved.

CN119764402AActive Publication Date: 2025-04-04SVOLT ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411965864.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The electrical performance of batteries prepared by existing silicon-carbon materials is not ideal, especially in terms of rate performance and cycle performance.

Method used

A silicon-carbon composite material is used, including the core and the cladding. The core consists of porous silicon and partially filled with the first amorphous carbon, and the cladding layer consists of a second amorphous carbon and a lithium-containing inorganic substance, which is coated on at least part of the surface of the core after being combined.

Benefits of technology

By reducing the interface impedance of silicon-carbon materials, the electronic conductivity is improved; by forming the coating layer, the ionic conductivity is improved, thereby significantly improving the rate performance and cycling performance of silicon-carbon composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764402A_ABST
    Figure CN119764402A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-carbon composite material, a preparation method and a battery. The silicon-carbon composite material comprises an inner core, the inner core comprises a silicon-carbon material, the silicon-carbon material comprises porous silicon, and at least part of the porous silicon is filled with first amorphous carbon; the coating layer comprises second amorphous carbon and a lithium-containing inorganic matter, and the second amorphous carbon and the lithium-containing inorganic matter are compounded and then coat at least part of the surface of the inner core. The silicon-carbon material formed by filling pores of porous silicon with amorphous carbon has relatively low interface impedance, the electronic conductivity of the composite material can be improved, in addition, the ionic conductivity of the material can be improved by a composite coating layer formed by the lithium-containing inorganic matter in the coating layer and the amorphous carbon, and the lithium-containing inorganic matter and the amorphous carbon are combined, so that the conductivity of the material is improved. And the rate capability and the cycle performance of the silicon-carbon composite material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of battery materials, and specifically relates to a silicon-carbon composite material, a preparation method, and a battery. Background Art

[0002] Silicon materials have the advantages of high theoretical specific capacity, low lithium insertion potential, abundant raw materials, non-toxicity and environmental protection. Silicon-carbon materials, by combining silicon and carbon, have the advantages of high specific capacity, long cycle life and excellent conductivity. They are expected to be used as the negative electrode material of the next generation of high-performance lithium-ion batteries to improve the battery's energy storage capacity and working performance, and meet the needs of electric vehicles, mobile electronic devices, etc. for high energy density and fast charging.

[0003] Although silicon-carbon materials have advantages such as high specific capacity, the silicon particles are easily agglomerated and pulverized, which affects the cycle performance and rate performance of the battery. Therefore, how to provide a new type of silicon-carbon material with ideal rate performance and cycle performance is a problem that needs to be solved at present. Summary of the invention

[0004] The present application provides a silicon-carbon composite material and a preparation method and a battery, aiming to solve the problem of unsatisfactory electrical performance of batteries prepared from existing silicon-carbon materials.

[0005] A first embodiment of the present application provides a silicon-carbon composite material, comprising:

[0006] A core, the core comprising a silicon-carbon material, the silicon-carbon material comprising porous silicon, at least a portion of the porous silicon being filled with a first amorphous carbon;

[0007] The coating layer comprises a second amorphous carbon and a lithium-containing inorganic substance, and the second amorphous carbon and the lithium-containing inorganic substance are composited and coated on at least a portion of the surface of the inner core.

[0008] In some embodiments, the core further includes hollow carbon spheres, and the hollow carbon spheres and the silicon-carbon material are connected via a coupling agent.

[0009] In some embodiments, the tap density of the silicon-carbon composite material is 0.9 to 1.0 g / cm 3 .

[0010] In some embodiments, the specific surface area of ​​the silicon-carbon composite material is 1.5 to 3.5 m 2 / g.

[0011] In some embodiments, the porosity of the silicon-carbon composite material is 20% to 50%.

[0012] In some embodiments, the silicon-carbon composite material has a silicon grain size of 1 to 2 nm.

[0013] In some embodiments, the mass ratio of the core to the coating layer is 95-98:2-5.

[0014] In some embodiments, the coupling agent includes at least one of N,N-diethylaminopropyltrimethoxysilane and N,N-diethylaminopropyltrichlorosilane.

[0015] In some embodiments, the lithium-containing inorganic material includes at least one of lithium carbonate, lithium niobate, and lithium hydroxide.

[0016] A second embodiment of the present application provides a method for preparing a silicon-carbon composite material, which is used to prepare the silicon-carbon composite material in any of the above embodiments, comprising the following steps:

[0017] Providing a silicon alloy, and etching the silicon alloy to obtain porous silicon;

[0018] Passing a carbon source gas into the porous silicon and performing a first heat treatment so that the carbon source gas forms a first amorphous carbon which is deposited in the micropores of the porous silicon to obtain a silicon-carbon precursor;

[0019] The silicon-carbon precursor is uniformly mixed with hollow carbon spheres, a coupling agent, and an organic acid, and then mixed with a lithium-containing inorganic substance, and subjected to a second heat treatment to obtain the silicon-carbon composite material.

[0020] In some embodiments, before the step of etching the silicon alloy, the method further comprises:

[0021] A mixed gas of oxygen and nitrogen is introduced to oxidize the surface of the silicon alloy to obtain a silicon alloy coated with silicon dioxide.

[0022] In some embodiments, the mass ratio of the silicon alloy to the oxygen is 100:100-500.

[0023] In some embodiments, the volume ratio of the oxygen to the nitrogen is 1 to 5:10.

[0024] In some embodiments, the oxidation temperature is 50-200° C. and the time is 1-3 hours.

[0025] In some embodiments, the flow rate of the mixed gas is 10-100 ml / min.

[0026] In some embodiments, the step of uniformly mixing the silicon-carbon precursor with the hollow carbon spheres, the coupling agent, and the organic acid further comprises:

[0027] Adding the silicon-carbon precursor, the hollow carbon spheres and the coupling agent to the aqueous solution of the organic acid, dispersing them evenly, and spray drying them;

[0028] Wherein, the mass percentage of organic acid in the aqueous solution of organic acid is 1-5%.

[0029] In some embodiments, the mass ratio of the porous silicon to the carbon source gas is 90-95:5-10.

[0030] In some embodiments, the mass ratio of the silicon-carbon precursor, the hollow carbon sphere, the coupling agent and the organic acid is 100:10-50:1-5:1-5.

[0031] In some embodiments, the first heat treatment is performed at a temperature of 600 to 900° C. for a time of 30 to 300 min.

[0032] In some embodiments, the flow rate of the carbon source gas is 10-50 ml / min.

[0033] In some embodiments, the second heat treatment is performed at a temperature of 600 to 900° C. for 30 to 300 minutes.

[0034] In some embodiments, the silicon alloy includes at least one of silicon-aluminum alloy, silicon-ferroalloy, silicon-manganese alloy, silicon-nickel alloy and silicon-magnesium alloy, wherein the mass percentage of silicon element in the silicon alloy is 50-90%.

[0035] In some embodiments, the carbon source gas includes at least one of methane, ethane, acetylene, and ethylene.

[0036] In some embodiments, the coupling agent includes at least one of N,N-diethylaminopropyltrimethoxysilane and N,N-diethylaminopropyltrichlorosilane.

[0037] In some embodiments, the organic acid comprises at least one of adipic acid, oxalic acid, malonic acid, succinic acid, tartaric acid, benzoic acid, and phenylacetic acid.

[0038] In some embodiments, the lithium-containing inorganic material includes at least one of lithium carbonate, lithium niobate, and lithium hydroxide.

[0039] A third embodiment of the present application provides a battery, comprising a negative electrode sheet, wherein the negative electrode sheet comprises the silicon-carbon composite material in any of the above embodiments or the silicon-carbon composite material prepared by the preparation method in any of the above embodiments.

[0040] The present application provides a silicon-carbon composite material, comprising: a core, the core comprising a silicon-carbon material, the silicon-carbon material comprising porous silicon, at least part of the porous silicon being filled with a first amorphous carbon; a coating layer, the coating layer comprising a second amorphous carbon and a lithium-containing inorganic substance, the second amorphous carbon and the lithium-containing inorganic substance being composited and coated on at least part of the surface of the core. The silicon-carbon material formed by filling amorphous carbon in the pores of the porous silicon has a lower interface impedance, which can improve the electronic conductivity of the composite material. In addition, the composite coating layer formed by the lithium-containing inorganic substance and the amorphous carbon in the coating layer can improve the ionic conductivity of the material. The combination of the two can improve the rate performance and cycle performance of the silicon-carbon composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] The technical solution and other beneficial effects of the present application will be made apparent by describing in detail the specific implementation methods of the present application in conjunction with the accompanying drawings.

[0042] Figure 1 This is a SEM characterization image of a silicon-carbon composite material provided in Example 1 of the present application. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0044] In the description of the present application, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or can communicate with each other; it can be directly connected, or indirectly connected through an intermediate medium, or indirectly connected through a pipe or pipeline, and it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to the specific circumstances. In the description of the present application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. In addition, the terms "first" and "second" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" can explicitly or implicitly include one or more features.

[0045] Silicon-carbon material is a key material with great potential and research value in the field of batteries, especially lithium-ion batteries. By combining silicon and carbon, carbon materials can provide a good conductive network for silicon and improve the efficiency of electron transmission. At the same time, its own structural stability can effectively buffer the volume expansion of silicon during the charging and discharging process and inhibit the agglomeration and pulverization of silicon particles. In addition, silicon-carbon material can also combine the advantages of silicon and carbon, while maintaining a high specific capacity, taking into account good conductivity, chemical stability and processing performance.

[0046] Silicon-carbon materials are usually composed of porous carbon and nanosilicon deposited in its pores, and are passivated on their surface to obtain silicon-carbon materials. However, due to problems such as large interface impedance between nanosilicon and porous carbon, the improvement in rate performance and cycle performance of silicon-carbon materials is not ideal.

[0047] Therefore, the inventors found through research that changing the traditional deposition of nano-silicon in porous carbon to deposition of amorphous carbon in porous silicon can effectively reduce the interface impedance between silicon and carbon in the obtained carbon-silicon material, thereby improving the cycle performance and rate performance of the silicon-carbon material; in addition, the inventors also found that coating amorphous carbon on the surface of the silicon-carbon material can also play a role in preventing the volume expansion of the silicon material and reducing the pulverization and shedding of the electrode material during the cycle. At the same time, the amorphous carbon coating can further provide a good conductive network, improve the transmission efficiency of electrons in the electrode material, and improve the electronic conductivity of the composite material. Based on this, the inventors proposed a silicon-carbon composite material, a preparation method, and a battery, aiming to solve the problem of unsatisfactory electrical performance of batteries made of existing silicon-carbon materials.

[0048] A first embodiment of the present application provides a silicon-carbon composite material, comprising:

[0049] A core, the core comprising a silicon-carbon material, the silicon-carbon material comprising porous silicon, at least a portion of the porous silicon being filled with a first amorphous carbon;

[0050] The coating layer includes a second amorphous carbon and a lithium-containing inorganic substance. The second amorphous carbon and the lithium-containing inorganic substance are composited and coated on at least a portion of the surface of the inner core.

[0051] It is understandable that porous silicon has a porous structure, which includes micropores, mesopores and macropores. Among them, micropores are holes with a pore size less than 2nm, mesopores are holes with a pore size between 2 and 50nm, and macropores are holes with a pore size greater than 50nm. Micropores, mesopores and macropores can constitute channels, and an interconnected network can be formed between the channels, which is conducive to mass transfer. The first amorphous carbon is filled in the porous structure, and the first amorphous carbon and the second amorphous carbon are the same in material, and the only difference is that the two exist in different positions in the silicon-carbon composite material. Amorphous carbon is a transitional carbon, generally in the form of porous black blocks or powders, with a small density and a large specific surface area, so it can effectively buffer the expansion caused by silicon materials. The silicon-carbon material formed by filling amorphous carbon in the pores of porous silicon has a lower interface impedance and can improve the electronic conductivity of the composite material. In addition, the composite coating layer formed by the lithium-containing inorganic substance and amorphous carbon in the coating layer can improve the ionic conductivity of the material. The combination of the two can improve the rate performance of the silicon-carbon composite material.

[0052] In some embodiments, the core further includes hollow carbon spheres, and the hollow carbon spheres and the silicon-carbon material are connected via a coupling agent.

[0053] On the one hand, hollow carbon spheres can enhance the conductivity of composite materials, and on the other hand, they can be connected with silicon-carbon materials to form a secondary particle structure, which can provide a buffer for the deformation of silicon-carbon materials during the charge and discharge process of the battery, thereby reducing the expansion of the core and effectively improving the cycle performance of silicon-carbon composite materials. There are abundant functional groups on the surface of silicon-carbon materials and hollow carbon spheres, such as hydroxyl, carboxyl, carbonyl, etc. These functional groups can react chemically with the active groups in the coupling agent molecules to form chemical bonds such as covalent bonds or hydrogen bonds, thereby achieving effective connection between hollow carbon spheres and silicon-carbon materials. Through this connection method, the structural stability of the composite material can be significantly improved, so that during the charge and discharge process, the material can better resist the stress impact caused by the volume expansion of silicon, effectively reduce the pulverization and peeling of the electrode material, and at the same time enhance the smoothness of electron transmission, promote the rapid diffusion and insertion and extraction of lithium ions in the material, thereby improving the rate performance of the battery.

[0054] In some embodiments, the coupling agent is preferably an amino coupling agent, and the amino coupling agent includes at least one of N,N-diethylaminopropyltrimethoxysilane and N,N-diethylaminopropyltrichlorosilane.

[0055] The amino group in the amino coupling agent can react with functional groups such as carboxyl and hydroxyl on the surface of hollow carbon spheres and silicon-carbon materials to establish a stable chemical bond, further improving the stability of the combination of hollow carbon spheres and silicon-carbon materials, and can increase the bonding density between hollow carbon spheres and silicon-carbon materials, thereby increasing the overall tap density of the composite material; in addition, the nitrogen element in the amino coupling agent can act as a doping element to increase the conductivity of the inner core, thereby improving the electronic conductivity of the silicon-carbon composite material.

[0056] In some embodiments, the tap density of the silicon-carbon composite material is 0.9 to 1.0 g / cm 3 .

[0057] It is understandable that the tap density of the silicon-carbon composite material (unit: g / cm 3 ) can be any value among 0.9, 0.92, 0.94, 0.96, 0.98, 1.0 or a range between any two values. When the tap density of the silicon-carbon composite material meets the above value range, the battery has relatively ideal cycle stability and rate performance.

[0058] In some embodiments, the specific surface area of ​​the silicon-carbon composite material is 1.5 to 3.5 m 2 / g.

[0059] It is understandable that the specific surface area of ​​the silicon-carbon composite material (unit: m 2 / g) can be any value among 1.5, 2.0, 2.5, 3.0, 3.5 or a range between any two values. When the specific surface area of ​​the silicon-carbon composite material meets the above value range, the silicon-carbon composite material has good energy density and reaction activity.

[0060] In some embodiments, the silicon grain size of the silicon-carbon composite material is 1-2 nm.

[0061] It is understandable that the value of the silicon grain size of the silicon-carbon composite material (unit: nm) can be any value among 1, 1.2, 1.4, 1.6, 1.8, 2, or a range between any two values. The silicon grain size refers to the particle size formed by silicon crystals in the silicon-carbon composite material. Smaller silicon grains can reduce the expansion of the silicon-carbon material, thereby improving the rate performance of the battery.

[0062] In some embodiments, the porosity of the silicon-carbon composite material is 20% to 50%.

[0063] It is understandable that the porosity of the silicon-carbon composite material can be any value among 20%, 25%, 30%, 35%, 40%, 45%, 50, or a range between any two values. In terms of lithium ion transmission, the pores in the silicon-carbon composite material can provide diffusion channels, which are conducive to the rapid insertion and removal of lithium ions. Among them, too high or too low porosity will increase the diffusion resistance. In addition, pores of appropriate size and density can also provide buffer space for the volume change of silicon. If the porosity is too high or too low, there is a risk of damaging the electrode structure. When the porosity of the silicon-carbon composite material meets the above range of values, the silicon-carbon composite material has good cycle performance and ion transmission capability.

[0064] In some embodiments, the mass ratio of the core to the coating layer is 95-98:2-5.

[0065] It is understandable that the mass ratio of the core to the coating layer can be any value among 95:5, 96:4, 97:3, 98:2 or a range between any two values. When the mass ratio of the core to the coating layer meets the above range, the high capacity characteristics of the silicon-carbon material and the hollow carbon sphere can be fully utilized to improve the energy density of the battery, while ensuring that the coating layer has sufficient thickness to play a good protective role on the core, reduce the adverse effects of the volume expansion of silicon during the charge and discharge process, and improve the cycle stability of the material.

[0066] In some embodiments, the lithium-containing inorganic material includes at least one of lithium carbonate, lithium niobate, and lithium hydroxide.

[0067] The above lithium-containing inorganic substances have an ionic crystal structure with a stable crystal structure, a strong ionic bond, and good ion migration ability, so that lithium ions can migrate relatively quickly in the electrolyte.

[0068] A second embodiment of the present application provides a method for preparing a silicon-carbon composite material, which is used to prepare the silicon-carbon composite material in any of the above embodiments, comprising the following steps:

[0069] Providing a silicon alloy, and etching the silicon alloy to obtain porous silicon;

[0070] A carbon source gas is introduced into the porous silicon to perform a first heat treatment, so that the carbon source gas forms a first amorphous carbon which is deposited in the micropores of the porous silicon to obtain a silicon-carbon precursor;

[0071] The silicon-carbon precursor is uniformly mixed with hollow carbon balls, a coupling agent and an organic acid, and then mixed with a lithium-containing inorganic substance, and subjected to a second heat treatment to obtain a silicon-carbon composite material.

[0072] The preparation method provided in the present application uses silicon alloy as silicon raw material to prepare porous silicon, and then deposits the first amorphous carbon in the pores of the porous silicon by vapor deposition, which can significantly improve the bonding strength between silicon and carbon, avoid the phenomenon of silicon material falling off easily during the long-term cycle of the battery, and affect the stability and service life of the electrode. The mechanical properties of silicon alloy are easy to control. In the process of preparing porous silicon, the pore size, porosity and other structural parameters of porous silicon can be controlled by adjusting the alloy composition and process parameters, so that the silicon-carbon composite material meets different porosity, tap density, specific surface area and other performance requirements, and is suitable for different battery application scenarios; secondly, using inorganic acid to sinter with lithium-containing inorganic matter and other reaction raw materials in a tubular furnace, the inorganic acid can react with the lithium-containing inorganic matter to form a second amorphous carbon and a coating layer composited with the lithium-containing inorganic matter, which not only increases the overall mechanical strength and stability of the silicon-carbon composite material, but also improves the ionic conductivity of the silicon-carbon composite material.

[0073] In some embodiments, before the step of etching the silicon alloy, the method further comprises:

[0074] A mixed gas of oxygen and nitrogen is introduced to oxidize the surface of the silicon alloy to obtain a silicon alloy coated with silicon dioxide.

[0075] By forming an oxide layer on the surface of the silicon alloy before the etching step, the etching rate can be adjusted, the micropores formed by etching can be more uniform, and the prepared porous silicon can have good mechanical strength, avoiding breakage in subsequent processes that affects the electrical properties of the composite material.

[0076] In some embodiments, the mass ratio of silicon alloy to oxygen is 100:100-500.

[0077] It can be understood that the mass ratio of silicon alloy to oxygen can be any value of 100:100, 100:200, 100:300, 100:400, 100:500 or a range between any two values.

[0078] In some embodiments, the volume ratio of oxygen to nitrogen is 1 to 5:10.

[0079] It is understood that the volume ratio of oxygen to nitrogen is any value of 1:10, 1:5, 3:10, 2:5, 1:2 or a range between any two values. When the mass ratio of silicon alloy to oxygen and the volume ratio of oxygen to nitrogen meet the above ranges, a uniform and dense silicon dioxide coating layer can be formed on the surface.

[0080] In some embodiments, the oxidation temperature is 50-200° C. and the oxidation time is 1-3 hours.

[0081] It can be understood that the oxidation temperature (unit: ℃) can be any value among 50, 100, 150, 200 or a range between any two values, and the oxidation time (unit: h) can be any value among 1, 1.5, 2, 2.5, 3 or a range between any two values.

[0082] In some embodiments, the flow rate of the mixed gas is 10-100 ml / min.

[0083] It can be understood that the flow rate of the mixed gas (unit: ml / min) can be any value of 10, 20, 30, 40, 50, 60, 70, 80, 90, 100 or a range between any two values.

[0084] In some embodiments, the step of uniformly mixing the silicon-carbon precursor with the hollow carbon spheres, the coupling agent, and the organic acid further comprises:

[0085] Adding silicon-carbon precursor, hollow carbon spheres and coupling agent into an aqueous solution of organic acid, dispersing them evenly, and spray drying;

[0086] The mass percentage of the organic acid in the aqueous solution of the organic acid is 1 to 5%.

[0087] The silicon-carbon precursor, hollow carbon spheres, coupling agent and organic acid solution are evenly mixed and then spray-dried, and then mixed with lithium-containing inorganic substances and then enter into a tubular furnace for continuous reaction of heat treatment, so that the mixing between the reaction materials is more uniform, thereby making the bonding between the silicon-carbon precursor and the hollow carbon spheres, and between the lithium-containing inorganic substances and the amorphous carbon formed by the heating of the organic acid tighter, and the pores and particle sizes of the formed silicon-carbon composite material are more uniform, thereby improving the energy density and cycle performance of the silicon-carbon composite material.

[0088] It can be understood that the mass percentage of the organic acid in the aqueous solution of the organic acid can be any value of 1%, 2%, 3%, 4%, 5%, or a range between any two values.

[0089] Specifically, the method for preparing the silicon-carbon composite material provided in the embodiment of the present application can be achieved by the following steps:

[0090] S1, placing the silicon alloy in a tube furnace, exhausting the air in the tube, and then introducing a mixed gas of oxygen and nitrogen to oxidize the silicon alloy material to obtain a silicon dioxide-coated silicon alloy material, and then etching the silicon dioxide-coated silicon alloy material with an etching solution, washing with water, and obtaining porous silicon;

[0091] S2. Under the condition of dew point ≤ -50°C, the porous silicon is transferred to a tube furnace, an inert gas is introduced to exhaust the air in the tube, the temperature is increased, a carbon source gas is introduced, and a first heat treatment is performed to obtain a silicon-carbon precursor;

[0092] S3. Add the silicon-carbon precursor, hollow carbon spheres and amino coupling agent to an organic acid aqueous solution and disperse them evenly, spray-dry the mixed solution to obtain an intermediate material; then mix the intermediate material with a lithium-containing inorganic substance to obtain a mixed powder, transfer it to a tubular furnace, increase the temperature, introduce the mixed powder, and perform a second heat treatment to obtain a silicon-carbon composite material.

[0093] In some embodiments, the mass ratio of porous silicon to carbon source gas is 90-95:5-10.

[0094] In some embodiments, the mass ratio of the silicon-carbon precursor, the hollow carbon sphere, the coupling agent and the organic acid is 100:10-50:1-5:1-5.

[0095] In some embodiments, the first heat treatment is performed at a temperature of 600-900° C. for a time of 30-300 min.

[0096] It can be understood that the temperature of the first heat treatment (unit: ℃) can be any value among 600, 650, 700, 750, 800, 850, 900 or a range between any two values, and the time of the first heat treatment (unit: min) can be any value among 30, 50, 100, 150, 200, 250, 300 or a range between any two values.

[0097] In some embodiments, the flow rate of the carbon source gas is 10-50 ml / min.

[0098] It can be understood that the flow rate of the carbon source gas (unit: ml / min) can be any value among 10, 20, 30, 40, 50 or a range between any two values.

[0099] In some embodiments, the second heat treatment is performed at a temperature of 600 to 900° C. for a time of 30 to 300 min.

[0100] It can be understood that the temperature of the second heat treatment (unit: ℃) can be any value among 600, 650, 700, 750, 800, 850, 900 or a range between any two values, and the time of the second heat treatment (unit: min) can be any value among 30, 50, 100, 150, 200, 250, 300 or a range between any two values.

[0101] In some embodiments, the silicon alloy includes at least one of silicon-aluminum alloy, silicon-ferroalloy, silicon-manganese alloy, silicon-nickel alloy and silicon-magnesium alloy, wherein the mass percentage of silicon element in the silicon alloy is 50-90%.

[0102] It can be understood that the mass percentage of silicon in the silicon alloy can be any value of 50%, 60%, 70%, 80%, 90% or a range between any two values.

[0103] In some embodiments, the carbon source gas includes at least one of methane, ethane, acetylene, and ethylene.

[0104] In some embodiments, the coupling agent includes at least one of N,N-diethylaminopropyltrimethoxysilane and N,N-diethylaminopropyltrichlorosilane.

[0105] In some embodiments, the organic acid comprises at least one of adipic acid, oxalic acid, malonic acid, succinic acid, tartaric acid, benzoic acid, and phenylacetic acid.

[0106] In some embodiments, the lithium-containing inorganic material includes at least one of lithium carbonate, lithium niobate, and lithium hydroxide.

[0107] A third embodiment of the present application provides a battery, including a negative electrode sheet, wherein the negative electrode sheet includes the silicon-carbon composite material in any of the above embodiments or includes the silicon-carbon composite material prepared by the preparation method in any of the above embodiments.

[0108] The following is a description of a silicon-carbon composite material, a preparation method, and a battery provided by the present application in conjunction with specific embodiments:

[0109] Example 1

[0110] This embodiment provides a silicon-carbon composite material, which is prepared by the following steps:

[0111] S1. 100 g of silicon-aluminum alloy was placed in a tube furnace, the air in the tube was exhausted, and then a mixed gas of oxygen and nitrogen (volume ratio of oxygen: nitrogen = 3:10) was introduced, the temperature in the furnace was controlled to be 100° C., the mixed gas flow rate was 50 ml / min, and the mixed gas was introduced for 2 h to oxidize and obtain a silicon dioxide-coated silicon alloy material, and then the silicon dioxide-coated silicon alloy material was etched with hydrofluoric acid (500 g, 47 wt%), and washed with water to obtain porous silicon;

[0112] S2. Under the condition of dew point -60°C, the porous silicon is transferred to a tube furnace, argon gas is first introduced to exhaust the air in the tube, the temperature is raised to 800°C, ethylene gas is introduced at a flow rate of 30 ml / min for 150 min, and the first heat treatment is performed to obtain a silicon-carbon precursor;

[0113] S3. Evenly mix 100 g of silicon-carbon precursor, 30 g of hollow carbon spheres and 3 g of N,N-diethylaminopropyltrimethoxysilane, and add them to an aqueous solution of adipic acid (100 g, 3 wt%) to disperse them evenly. Spray dry the mixed solution to obtain an intermediate material. Then, mix 100 g of the intermediate material with 5 g of lithium carbonate to obtain a mixed powder, and transfer it to a tubular furnace. Heat it to 800 ° C, pass the mixed powder at a flow rate of 30 ml / min, perform a second heat treatment, and react for 150 min to obtain a silicon-carbon composite material.

[0114] The silicon-carbon composite material prepared in this example was subjected to SEM scanning, and the scanning characterization diagram is as follows: Figure 1 As shown, it can be seen that the material presents a porous structure with a reasonable size distribution, and the particle size is between 5 and 10 μm.

[0115] Example 2

[0116] This embodiment provides a silicon-carbon composite material, which is prepared by the following steps:

[0117] S1. Place 100 g of silicon-manganese alloy in a tubular furnace, exhaust the air in the tube, then introduce a mixed gas of oxygen and nitrogen (volume ratio of oxygen: nitrogen = 1:10), control the temperature in the furnace to 50° C., and the mixed gas flow rate to 10 ml / min. The mixture is introduced for 3 h to oxidize and obtain a silicon alloy material coated with silicon dioxide. Then, the silicon alloy material coated with silicon dioxide is etched with hydrofluoric acid (500 g, 47 wt%), and washed with water to obtain porous silicon.

[0118] S2. Under the condition of dew point -60°C, the porous silicon is transferred to a tube furnace, argon gas is first introduced to exhaust the air in the tube, the temperature is raised to 600°C, acetylene gas is introduced at a flow rate of 10 ml / min for 300 min, and the first heat treatment is performed to obtain a silicon-carbon precursor;

[0119] S3. Evenly mix 100 g of silicon-carbon precursor, 10 g of hollow carbon spheres and 1 g of N,N-diethylaminopropyltrichlorosilane, and add them to an aqueous solution of oxalic acid (100 g, 1 wt%) to disperse them evenly. Spray dry the mixed solution to obtain an intermediate material. Then, mix 100 g of the intermediate material with 1 g of lithium hydroxide to obtain a mixed powder, and transfer it to a tubular furnace. Heat it to 600 ° C, pass the mixed powder at a flow rate of 100 ml / min, perform a second heat treatment, and react for 300 min to obtain a silicon-carbon composite material.

[0120] Example 3

[0121] This embodiment provides a silicon-carbon composite material, which is prepared by the following steps:

[0122] S1. Place 100 g of silicon-magnesium alloy in a tube furnace, exhaust the air in the tube, then introduce a mixed gas of oxygen and nitrogen (volume ratio of oxygen: nitrogen = 1:2), control the temperature in the furnace to 200° C., and the mixed gas flow rate to 100 ml / min. The mixed gas is introduced for 1 hour for oxidation to obtain a silicon dioxide-coated silicon alloy material, and then use hydrofluoric acid (500 g, 47 wt%) to etch the silicon dioxide-coated silicon alloy material, and wash with water to obtain porous silicon;

[0123] S2. Under the condition of dew point -60°C, the porous silicon is transferred to a tube furnace, argon gas is first introduced to exhaust the air in the tube, the temperature is raised to 900°C, ethylene gas is introduced at a flow rate of 50 ml / min for 30 minutes, and the first heat treatment is performed to obtain a silicon-carbon precursor;

[0124] S3. Evenly mix 100 g of silicon-carbon precursor, 50 g of hollow carbon spheres and 5 g of N,N-diethylaminopropyltrimethoxysilane, and add them to an aqueous solution of adipic acid (100 g, 5 wt%) to disperse them evenly. Spray dry the mixed solution to obtain an intermediate material. Then, mix 100 g of the intermediate material with 10 g of lithium niobate to obtain a mixed powder, and transfer it to a tubular furnace. Heat it to 900 ° C, introduce the mixed powder at a flow rate of 50 ml / min, perform a second heat treatment, and react for 30 minutes to obtain a silicon-carbon composite material.

[0125] Example 4

[0126] The method for preparing the silicon-carbon composite material provided in Example 4 is consistent with that in Example 1, except that only oxygen is introduced in step S1.

[0127] Example 5

[0128] The method for preparing the silicon-carbon composite material provided in Example 5 is consistent with that in Example 1, except that the amount of hollow carbon spheres added in step S3 is changed to 100 g, and the rest is the same as in Example 1.

[0129] Comparative Example 1

[0130] The preparation method of the silicon-carbon composite material provided in Comparative Example 1 is basically the same as that in Example 1, except that hollow carbon spheres and coupling agent N,N-diethylaminopropyltrimethoxysilane are not added in step S3, and the rest is the same as that in Example 1.

[0131] Comparative Example 2

[0132] The method for preparing the silicon-carbon composite material provided in Comparative Example 2 is basically the same as that in Example 1, except that lithium carbonate is not added in step S3, and the rest is the same as that in Example 1.

[0133] Comparative Example 3

[0134] In the silicon-carbon composite material provided in Comparative Example 3, the silicon-carbon material is obtained by depositing nano-silicon in porous carbon.

[0135] The preparation method of silicon carbon material is as follows:

[0136] Porous carbon was put into the cavity of a fluidized bed equipment, and a silane / nitrogen mixed gas (the volume ratio of silane:nitrogen was 10:1) was introduced into the cavity. Nano-silicon deposition was achieved for 3 hours at a temperature of 500°C and a gas flow rate of 500 ml / min. The temperature was then raised to 700°C, and acetylene was introduced into the cavity at a flow rate of 300 ml / min for 150 minutes to obtain a silicon-carbon material.

[0137] The other steps are the same as those in Example 1.

[0138] Silicon-carbon composite material performance test:

[0139] The silicon-carbon composite materials in the above-mentioned embodiments and comparative examples were tested for tap density, specific surface area, silicon grain size, powder resistivity, porosity, gas production and specific capacity as well as initial efficiency.

[0140] Test method: The powder resistivity is tested by a four-probe tester; m1g of powder material is added to a 10% sodium hydroxide aqueous solution and soaked at 45°C for 48 hours, and then the gas production V1 is tested, and then the gas production = V1 / m1*100% is calculated. Other test items are tested in accordance with GB / T38823-2020 "Silicon Carbon"; silicon grains are obtained by XRD test, and the test results are shown in Table 1.

[0141] Table 1

[0142]

[0143] According to Table 1, it can be seen that the silicon-carbon composite material prepared by the preparation method in the scheme provided by the present application, the process parameters are adjusted in the process parameter value range provided in the present application, and the silicon-carbon composite material can have an ideal tap density, specific surface area, silicon grain size and porosity. According to Example 4, it can be seen that when nitrogen is not introduced into the process of oxidizing the surface of the silicon alloy, the compactness of the porous silicon surface will be affected to a certain extent, thereby making the final silicon-carbon composite material have a low porosity. According to Example 5, it can be seen that excessive addition of hollow carbon balls may cause the porosity to be high. According to Comparative Examples 1-2, it can be seen that not adding hollow carbon balls or not adding lithium-containing inorganic substances will result in a low tap density. According to Comparative Example 3, it can be seen that the use of porous carbon to deposit nano-silicon to prepare silicon-carbon materials will result in excessive silicon grains and low porosity.

[0144] Preparation of button cells:

[0145] The silicon-carbon composite materials in the above embodiments and comparative examples are used as negative electrode materials for lithium-ion batteries and assembled into button batteries A1, A2, A3, A4, A5, B1, B2, and B3. The preparation method thereof is as follows: a binder, a conductive agent, and a solvent are added to the negative electrode material, stirred to make a slurry, coated on a copper foil, and dried and rolled to obtain the result. The binder used is LA136D binder, the conductive agent is SP, the negative electrode material is the negative electrode material prepared in Examples 1-5 and Comparative Examples 1-3, respectively, the solvent is double distilled water, and the ratio is: negative electrode material: SP: LA136D: double distilled water = 90g: 5g: 4g: 250mL, and a negative electrode sheet is prepared; the electrolyte is LiPF6 / EC+DEC (volume ratio 1: 1, concentration 1.3mol / L), the metal lithium sheet is the counter electrode, the diaphragm is polyethylene (PE), the simulated battery assembly is carried out in an argon-filled glove box, and the electrochemical performance is carried out on a Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 0.00V to 2.0V and a charge and discharge rate of 0.1C. At the same time, the rate (1C, 0.1C) and cycle performance (0.1C / 0.1C, 100 weeks) of its button battery are tested. The test data are shown in Table 2.

[0146] Table 2

[0147]

[0148] It can be seen from Table 2 that the porous silicon-carbon composite materials prepared in Examples 1-5 have high first efficiency and rate performance. The reason is that coating the lithium compound on the surface of the material improves the ionic conductivity of the material and reduces its irreversible capacity, thereby improving the first efficiency and its rate performance; at the same time, doping hollow carbon spheres, relying on their own low expansion characteristics, reduces the expansion of the silicon-carbon composite material and improves the cycle performance.

[0149] Preparation of soft pack battery:

[0150] The negative electrode sheet was prepared by mixing 8% of silicon-carbon material with the silicon-carbon composite materials in the above embodiment and the comparative example. 1 / 3 Co 1 / 3 Mn 1 / 3 O2) as the positive electrode, LiPF6 (solvent is EC+DEC, volume ratio is 1:1, concentration is 1.3 mol / l) as the electrolyte and celegard2400 as the separator to prepare 5Ah soft-pack batteries C1, C2, C3, C4, C5 and D1, D2, D3, that is, ternary soft-pack lithium batteries are obtained. The test results are detailed in Tables 2 and 3.

[0151] The rate performance of the soft-pack battery was tested with a charge and discharge voltage range of 2.5-4.2V and a temperature of 25±3.0℃. It was charged to 4.2V at a rate of 1C, and then charged at a constant current of 0.1A for 4h at a constant voltage of 4.2V. The constant current ratio = constant current capacity / (constant current capacity + constant voltage capacity) was calculated. At the same time, the full charge expansion of the soft-pack battery at 100% SOC was tested. The test results are shown in Table 3.

[0152] At the same time, the cycle performance of soft pack batteries C1 / C2 / C3 / C4 / C5 / D1 / D2 / D3 was tested under the following test conditions: charge and discharge voltage range of 2.5-4.2V, temperature of 25±3.0℃, charge and discharge rate of 1.0C / 1.0C, and cycle number of 500 times. The test results are shown in Table 3.

[0153] Table 3

[0154]

[0155] It can be seen from Table 3 that the cycle performance and rate performance of the lithium-ion battery of the soft-pack lithium-ion battery prepared using the silicon-carbon composite material of the present invention are significantly better than those of the comparative example. The reason is that the embodiment material is doped with inorganic lithium salt to improve the ionic conductivity of the material, so that the expansion of the material is lower, thereby improving the cycle performance.

[0156] The above is a detailed introduction to a silicon-carbon composite material, a preparation method, and a battery provided in the embodiments of the present application. Specific examples are used in the present application to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solution and its core idea of ​​the present application. Ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein with equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A silicon-carbon composite material, characterized in that: include: A core, the core comprising a silicon-carbon material, the silicon-carbon material comprising porous silicon, at least a portion of the porous silicon being filled with a first amorphous carbon; The coating layer comprises a second amorphous carbon and a lithium-containing inorganic substance, and the second amorphous carbon and the lithium-containing inorganic substance are composited and coated on at least a portion of the surface of the inner core.

2. A silicon-carbon composite material according to claim 1, characterized in that: The inner core further comprises a hollow carbon sphere, and the hollow carbon sphere and the silicon-carbon material are connected via a coupling agent.

3. The silicon-carbon composite material according to claim 1, characterized in that: The tap density of the silicon-carbon composite material is 0.9 to 1.0 g / cm 3 and / or, The specific surface area of ​​the silicon-carbon composite material is 1.5 to 3.5 m 2 / g; and / or, The porosity of the silicon-carbon composite material is 20% to 50%; and / or, The silicon-carbon composite material has a silicon grain size of 1 to 2.0 nm; and / or, The mass ratio of the core to the coating layer is 95-98:2-5.

4. A silicon-carbon composite material according to claim 2, characterized in that: The coupling agent includes at least one of N,N-diethylaminopropyltrimethoxysilane and N,N-diethylaminopropyltrichlorosilane; and / or, The lithium-containing inorganic substance includes at least one of lithium carbonate, lithium niobate and lithium hydroxide.

5. A method for preparing a silicon-carbon composite material according to any one of claims 1 to 4, characterized in that: The steps include: Providing a silicon alloy, and etching the silicon alloy to obtain porous silicon; Passing a carbon source gas into the porous silicon and performing a first heat treatment so that the carbon source gas forms a first amorphous carbon which is deposited in the micropores of the porous silicon to obtain a silicon-carbon precursor; The silicon-carbon precursor is uniformly mixed with hollow carbon spheres, a coupling agent, and an organic acid, and then mixed with a lithium-containing inorganic substance, and subjected to a second heat treatment to obtain the silicon-carbon composite material.

6. The method for preparing a silicon-carbon composite material according to claim 5, characterized in that: Before the step of etching the silicon alloy, the method further comprises: A mixed gas of oxygen and nitrogen is introduced to oxidize the surface of the silicon alloy to obtain a silicon dioxide-coated silicon alloy, which satisfies at least one of the following conditions: a) the mass ratio of the silicon alloy to the oxygen is 100:100-500; b) the volume ratio of the oxygen to the nitrogen is 1 to 5:10; c) the oxidation temperature is 50 to 200° C. and the time is 1 to 3 hours; d) The flow rate of the mixed gas is 10-100 ml / min.

7. The method for preparing a silicon-carbon composite material according to claim 5, characterized in that: The step of uniformly mixing the silicon-carbon precursor with the hollow carbon spheres, the coupling agent and the organic acid also includes: Adding the silicon-carbon precursor, the hollow carbon spheres and the coupling agent to the aqueous solution of the organic acid, dispersing them evenly, and spray drying them; Wherein, the mass percentage of organic acid in the aqueous solution of organic acid is 1-5%.

8. The method for preparing a silicon-carbon composite material according to claim 5, characterized in that: The mass ratio of the porous silicon to the carbon source gas is 90-95:5-10; and / or, The mass ratio of the silicon-carbon precursor, the hollow carbon sphere, the coupling agent and the organic acid is 100:10-50:1-5:1-5; and / or, The temperature of the first heat treatment is 600-900° C. and the time is 30-300 min; and / or, The flow rate of the carbon source gas is 10 to 50 ml / min; and / or, The temperature of the second heat treatment is 600-900° C., and the time is 30-300 minutes.

9. The method for preparing a silicon-carbon composite material according to claim 5, characterized in that: The silicon alloy comprises at least one of silicon-aluminum alloy, silicon-ferroalloy, silicon-manganese alloy, silicon-nickel alloy and silicon-magnesium alloy, wherein the mass percentage of silicon in the silicon alloy is 50-90%; and / or, The carbon source gas includes at least one of methane, ethane, acetylene and ethylene; and / or, The coupling agent includes at least one of N,N-diethylaminopropyltrimethoxysilane and N,N-diethylaminopropyltrichlorosilane; and / or, The organic acid comprises at least one of adipic acid, oxalic acid, malonic acid, succinic acid, tartaric acid, benzoic acid and phenylacetic acid; and / or, The lithium-containing inorganic substance includes at least one of lithium carbonate, lithium niobate and lithium hydroxide.

10. A battery comprising a negative electrode sheet, characterized in that: The negative electrode sheet comprises the silicon-carbon composite material as claimed in any one of claims 1 to 4 or the silicon-carbon composite material prepared by the preparation method as claimed in any one of claims 5 to 9.

Citation Information

Patent Citations

  • Lithium ion battery silicon-carbon negative electrode material and preparation method thereof

    CN104332632A

  • Silicon-carbon composite material for lithium ion battery, preparation method and application of silicon-carbon composite material

    CN104716312A

  • Silicon oxide-graphene composite material and preparation method therefor

    CN107492645A

  • Silicon-carbon composite negative electrode material and preparation method thereof

    CN107768625A

  • Silicon-carbon anode material and preparation method thereof

    CN109346696A

Cited By

  • High-rate silicon carbon material and preparation method thereof

    CN121063537A